ECONOMIC VALUE ADDED (EVA) AND LEVERAGE ANALYSIS TO MEASURE THE FINANCIAL PERFORMANCE OF CIGARETTE COMPANIES - Priantono, Seger; Khoirun, Nisa (Pusat Riset dan Inovasi Nasional, 2022)
Financial statements are reports that can be used as a reference tool in making financial decisions and assessing performance in a company. This study is aimed at analyzing the assessment of the financial performance of cigarette companies using Economic value added (EVA) and leverage ratios. This type of research is descriptive quantitative, with variables consisting of EVA, DAR, and DER. Data is sourced from secondary data by the method of collection using documentation. The sample of this study is the financial statements of three cigarette companies for 2013 – 2017. The data analysis method used is descriptive with EVA, DAR, and DER ratios. The results showed that the assessment of financial performance in the form of EVA all cigarette companies had good performance (positive EVA value), PT. Gudang Garam Tbk has a better performance than others, because the value of EVA every year tends to increase, DAR for PT. Wismilak Inti Makmur Tbk is in the good category, but the company's DAR ratio every year decreases to a ratio of 20%, the DER ratio of PT. Gudang Garam Tbk and PT. PT. Wismilak Inti Makmur Tbk with good criteria